Prevalence and Risk Factors of Hypertension in Hansposa VDC of Sunsari District, Nepal - Shrestha, Dhan Bahadur; Dhungel, Sunil (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Hypertension is defined as a systolic blood pressure (SBP) of 140 millimeter of mercury (mm of Hg) or more and a diastolic blood pressure (DBP) of 90 mm of Hg or more, or taking antihypertensive medication. Hypertension causes an increased work load on the heart and can cause damage to the blood vessels. The public awareness about hypertension in the villages of Nepal is low and no studies have been conducted earlier to elaborate the risk factors and prevalence of Hypertension in Hansposa village of Nepal. The aim of this study was to identify the prevalence of Hypertension and the risk factors associated with it in this village. Methods: A cross sectional survey (study) was carried out from September 25, 2014 to October 25, 2014 in order to know the prevalence and risk factor(s) of hypertension among people of Hansposa Village Development Committee (VDC), Sunsari, Nepal. Data were collected from both sexes by asking demographic details, habits like alcohol intake, smoking, exercise and education and examination of blood pressure, weight and height. The association of hypertension with age, sex, education, tobacco, alcohol consumption and body mass index (BMI) were estimated according to WHO standard criteria. Results: On analysis, the prevalence of hypertension was 37 % [95% CI=31-42(M: 55.1%; F: 26.7%)]. The prevalence of tobacco, alcohol consumption, and overweight/obesity was 31.3% (including past and present), 36.1%, and 31.9% respectively. Further analysis showed that there is significant association between hypertension and age, sex, alcohol consumption and physical inactivity (P<0.05) i.e. there is increasing trend in the prevalence of hypertension with increasing age [ χ2(chi square) for linear trend P = 0.000]. Conclusion: There is high prevalence of hypertension among people of Hansposa VDC; especially isolated diastolic blood pressure and is associated with age, sex, alcohol consumption and physical inactivity.